Medication error: prescription writing error in Outpatient Pharmacy, Hospital Teluk Intan - Khairuddin, Nurul Farahain; Abdul Rahim, Nazirah (2009)
Errors in medication are a major cause of patient morbidity and mortality across the medical spectrum. Each year, over 7,000 deaths in the US are attributed to medication errors, according to a recent report from the Institute of Medicine, and researchers have estimated that almost 60% of all adverse events are the result of medication errors. Still, few studies have examined these errors in outpatient pharmacy. Pharmacists have tremendous opportunities and responsibilities in preventing medication errors. Errors in prescription writing averaged 2 1/2 a day in a large New York teaching hospital, and one in five of the mistakes could have caused severe medical problems or death. The Albany Medical Center study found a prescription error rate of 3.13 per 1,000 orders written of the 905 errors, 522, or S7.7 percent, were "significant". This study aimed to evaluate the prescription writing error in outpatient. Information regarding magnitude of prescription writing error in outpatient pharmacy, types of prescription writing error, its potential harm to patient and factors of prescription writing error associated with the number of drugs in a prescription was collected from prescriptions in outpatient clinic, specialist clinic and emergency department in Hospital Teluk Intan, Perak. Data was collected from a sample of 200 prescriptions from outpatient pharmacy had been divided into each department by percentage of prescription in a month. A total of 1188 Prescriptions were recorded with mean errors per prescription of 3.38 ± 2.39 and mean summary of total errors detected in prescription was 3.00. The number of medication prescribed was 3. 73 ± 1.89. There were significant correlations (p<0.05) between factors associated with prescription writing errors. The highest types of prescription writing error were writing in trade name (38.90%), prescription written using abbreviations (23.80%) and ambiguous prescription (23.80% ), The most encountered prescription writing error in this study identified were improving practice in prescribing and assists prioritization, planning and delivery of services in the most resource in an effective way. This study found that patient safety still need to be improved. This will be used to formulate strategies that incorporate the pharmacists and may indicate for the development and design of protocol/guidelines which applicable to the institution.